Tax Amnesty Pemberian Keringanan Dan Pembebasan Sanksi Administrasi Pajak Kendaraan Bermotor - Andi Rustam; Andi Arifwangsa Adiningrat; Saida Said; Muhammad Nur; Nur Afni (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the tax amnesty granting relief and exemption from motor vehicle tax administration sanctions. The research method used is descriptive and tends to use analysis with a qualitative approach to describe the realization of motor vehicle tax receipts using tables and diagrams before and after tax amnesty which is then drawn conclusions. The results of this study indicate that the tax amnesty program also increases public awareness in paying motor vehicle taxes in Manggarai Regency. This Tax Amnesty program also increases Regional Original Income in the motor vehicle tax sector until the set target is achieved. Keywords: Motor Vehicle Tax, Tax Amnesty, and Administrative Sanctions